Lami and the Singing Fish - Mohammed, Hadiza; Odupute, Francis (Nigeria, 2022)
Lami lives in a fishing village with her single father Baba. One day Baba caught a fish so he asked Lami to clean it. To Lami's surprise, the fish began to sing to her and asked for a favour. In return, the fish promised to give her the treasures of the river. Lami must decide whether to grant the fish its request or forgo the treasures of the river...
Keywords: Adventure; Juvenile Fiction